Affecting factors the incidence of chronic energy deficiency (CED) in pregnant women - Nur Alfi Fauziah; Hellen Febriyanti (Universitas Aisyah Pringsewu, 2023)
Chronic Energy Deficiency (CED) is a condition due to lack of energy and protein intake or the occurrence of imbalance of energy and protein intake in completing the needs of the body that lasts for a long period of time. The prevalence rate in Lampung of CED risk in pregnant women was 21.3%, still below the National figure. The result of the pre-survey at the Ketapang Public Health Center based on data obtained by researchers from 53 pregnant women with CED was dominated by pregnant women age of less than 20 years and the first pregnancy was 32 pregnant women (60.37%). The research objective was to know the factors that influence the incidence of Chronic Energy Deficiency (CED) in Pregnant Women at the Ketapang Public Health Center in 2022. This research type is quantitative with a case-control design. The population in this study was 53 mothers with CED and 53 mothers who did not experience CED. The sample in this study was the entire population, namely, 53 mothers who experienced CED and 53 mothers who did not experience CED. The analysis used the chi-square test. Results from the study revealed that there is an age correlation (p-value: 0.012 OR: 3.29) and the incidence of anemia (p-value: 0.046 OR: 2.4) with chronic energy deficiency (SEZ) in pregnant women at the Ketapang Public Health Center in South Lampung Regency in 2022. And there is no parity correlation with chronic energy deficiency (CED) in pregnant women at the Ketapang Public Health Center of South Lampung Regency in 2022 (p-value: 0.09). It is expected for the Ketapang Public Health Center to increase socialization on how to prevent the occurrence of CED in pregnant women. Abstrak: Kekurangan Energi Kronik (KEK) adalah suatu keadaan akibat kekurangan asupan energi dan protein atau terjadinya ketidak seimbangan asupan energi dan protein dalam memenuhi kebutuhan tubuh yang berlangsung dalam jangka waktu yang lama. Angka prevalensi di Lampung risiko KEK pada ibu hamil sebesar 21,3%, masih dibawah angka Nasional. Hasil pra survey di Puskesmas Rawat Inap Ketapang Berdasarkan data yang diperoleh peneliti dari 53 ibu hamil dengan KEK didominasi oleh ibu hamil dengan usia kurang dari 20 tahun dan kehamilan yang pertama yaitu 32 ibu hamil (60,37%). Tujuan dilakukannya penelitian ini adalah untuk mengetahui Faktor–faktor yang mempengaruhi kejadian Kekurangan Energi kronik (KEK) pada Ibu Hamil Di Puskesmas Rawat Inap Ketapang Tahun 2022. Jenis penelitian ini adalah penelitian kuantitatif dengan desain case control. Populasi dalam penelitian ini adalah seluruh ibu hamil TM I di Puskesmas Rawat Inap Ketapang Tahun 2022 yang berjumlah 315. Sampel pada penelitian ini 53 ibu yang mengalami KEK dan 53 ibu tidak mengalami KEK. Analisis yang digunakan adalah uji chi square. Hasil dari penelitian Ada hubungan usia (p-value: 0,012 OR: 3,29) dan kejadian anemia (p value : 0,046 OR: 2,4) dengan Kejadian Kurang Energi Kronik (KEK) pada ibu hamil di Puskesmas Rawat Inap Ketapang Kabupaten Lampung Selatan Tahun 2022. Dan tidak ada hubungan paritas dengan Kejadian Kurang Energi Kronik (KEK) pada ibu hamil di Puskesmas Rawat Inap Ketapang Kabupaten Lampung Selatan Tahun 2022 (p-value: 0,09). bagi Puskesmas Rawat Inap Ketapang untuk meningkatkan sosialisasi tentang cara pencegahan kejadian KEK pada ibu hamil